2022
DOI: 10.1029/2021pa004372
|View full text |Cite
|
Sign up to set email alerts
|

An Outlook for the Acquisition of Marine Sedimentary Ancient DNA (sedaDNA) From North Atlantic Ocean Archive Material

Abstract: Studies incorporating sedimentary ancient DNA (sedaDNA) analyses to investigate paleo‐environments have increased considerably over the last few years, and the possibility of utilizing archived sediment cores from previous field campaigns could unlock an immense resource of sampling material for such paleo‐investigations. However, sedaDNA research is at a high risk of contamination by modern environmental DNA, as sub‐optimal sediment storage conditions may allow for contaminants (e.g., fungi) to grow and becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Basidiomycota and Ascomycota were detected, especially at KC06, and also occurred in the water column, suggesting they may survive in both environments. Careful interpretation is required, however, as especially fungi have been linked to contamination in sed aDNA from deep seafloor archive samples stored over many years prior to analyses (Selway et al., 2022), although our samples were freshly collected, thus the latter possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Basidiomycota and Ascomycota were detected, especially at KC06, and also occurred in the water column, suggesting they may survive in both environments. Careful interpretation is required, however, as especially fungi have been linked to contamination in sed aDNA from deep seafloor archive samples stored over many years prior to analyses (Selway et al., 2022), although our samples were freshly collected, thus the latter possibility seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Ancient environmental DNA (aDNA) uses eDNA methods and metabarcoding on sediment cores to reproduce temporal changes in pelagic plankton. Using cores from five sites in the North Atlantic, Selway et al 58 presented clear evidence of aDNA from the ubiquitous coccolithophore Emiliania huxleyi, demonstrating the potential of this technique but also highlighting the importance of minimising contamination during sample collection and storage.…”
Section: The Atlantic Science Blueprintmentioning
confidence: 99%
“…To date, studies employing aeDNA as a climate and biodiversity proxy in sediments mostly focused on lacustrine deposits (Nguyen et al, 2023), with a marked increase in aeDNA research on marine deposits observed recently (e.g., De Schepper et al, 2019;Selway et al, 2022;Zimmermann et al, 2020Zimmermann et al, , 2021, including latest reports of 1-million years old diatom DNA isolated from a marine sediment core (Armbrecht et al, 2022) and record 2-million years old DNA from Kap København formation, which in part includes old marine sediments (Kjaer et al, 2022). Although fossilizing taxa (e.g., foraminifera, diatoms, and coccolithophores) offer a well-established proxy for marine paleoclimate reconstructions, aeDNA adds to a deeper understanding of past ecosystem structure, capturing diversity beyond the fossilized repository and often complementing it (Lejzerowicz et al, 2013;Parducci et al, 2019).…”
Section: Introductionmentioning
confidence: 99%